Cathepsin K expression is increased in oral lichen planus. (6th May 2016) - Siponen, Maria; Bitu, Carolina Cavalcante; Al‐Samadi, Ahmed; Nieminen, Pentti; Salo, Tuula
Abstract : Background: Oral lichen planus (OLP) is an idiopathic T‐cell‐mediated mucosal inflammatory disease. Cathepsin K (Cat K) is one of the lysosomal cysteine proteases. It is involved in many pathological conditions, including osteoporosis and cancer. The expression and role of Cat K in OLP are unknown. Methods: Twenty‐five oral mucosal specimens diagnosed histopathologically as OLP and fourteen healthy controls (HC) were used to study the immunohistochemical (IHC) expression of Cat K. Colocalization of Cat K with CD1a, Melan‐A, CD68, CD45, mast cell tryptase (MCT), and Toll‐like receptors (TLRs) 4 and 9 were studied using double IHC and/or immunofluorescence (IF) staining. Expression of Cat K was also evaluated in OLP tissue samples before and after topical tacrolimus treatment. Results: Cat K was expressed in a higher percentage of cells in the epithelial zone, and the staining intensity was stronger in the stroma in OLP compared to controls ( P < 0.001). In OLP, Cat K was present mostly in melanocytes and macrophages and sporadically in basal keratinocytes, endothelial cells, and extracellularly. Cat K was found also in some fibroblasts in HC and OLP samples. Coexpression of Cat K and TLRs 4 and 9 was seen in some dendritic cells (presumably melanocytes) and macrophages. In OLP, tacrolimus treatment reduced the expression of Cat K in the epithelium but increased it in the stroma. Conclusions: These results suggest that Cat K is involved in the pathogenesis of OLP. Cat K possibly takes part in the modulation of matrix molecules and cellular receptors.